Teachers’ Emotional and Occupational Well-being Amid National Lockdown - Cleo, Albertus; Omidire, Margaret Funke; Muhammed, Shuaib Abolakale (Journal of Teaching and Learning, 2026)
Teachers' well-being affects the quality of education. The pandemic-related national lockdown and social isolation in South Africa, lasting for two and a half years, harmed teachers and the education sector. Teachers' emotional and occupational well-being changed with online and rotational instruction. This was because they were expected to support students and parents and acquire essential competencies and skills for online technology-based teaching and learning. This paper discusses a study on secondary school teachers' struggles during school closures. Ten teachers from Gauteng, South Africa, were purposively recruited, five from each public and private school, using a qualitative research approach and exploratory case study design. The Teacher Well-being conceptual framework provided a theoretical framework for well-being. The findings illuminate the mental, physical, and social well-being issues of the 10 secondary school instructors, their transition to online teaching, and their intrinsic and extrinsic coping techniques, such as social media and faith. The study showed why school governing bodies should focus on coping methods to promote teachers' well-being. In Gauteng, South Africa, there is little research on teachers' well-being during school closures. More research is needed to address teachers' emotional and occupational well-being and discover professional development support.